The traditional english teaching methodology and the development of productive skills with the students of 10th year of basic education at unidad educativa anexa a la Universidad Nacional de Loja. Academic period 2013 – 2014 - Sánchez Poma, Elsa del Rocío (2015)
The present research work titled: “THE TRADITIONAL ENGLISH TEACHING METHODOLOGY AND THE DEVELOPMENT OF PRODUCTIVE SKILLS WITH THE STUDENTS OF 10TH YEAR OF BASIC EDUCATION AT UNIDAD EDUCATIVA ANEXA A LA UNIVERSIDAD NACIONAL DE LOJA. ACADEMIC PERIOD 2013 – 2014” has been done with the purpose of determining if the traditional English teaching methodology is still used in the development of productive skills of the English language of this educative institution. To carry out this research work, it was necessary to use some methods; as the main one was, the scientific method which helped the researcher to get suitable information that supported and reinforced this work. The technique used to collect the data was the survey; it was applied to teachers and students through a questionnaire. Then it was necessary to tabulate, organize, represent graphically and interpret the data collected in order to be able to verify the hypotheses and present the conclusions and recommendations. Finally, the results of this research demonstrate that still exist the use of traditional methodology, concluding that teachers are using traditional English teaching methodology in their classes causing a limited development of productive skills in the students learning process.